Analisis Abreviasi dalam Iklan di Media Sosial Serta Dampaknya pada Pembelajaran Bahasa Indonesia di SMP Kelas VIII - Maleha, Adelia; Nawawi, Nawawi (GERAM, 2024)
The rapid advancement in technology has increased the use of abbreviations in online media advertisements. To capture the attention of target audiences who tend to have limited time and attention spans, abbreviations can be an effective approach. However, improper or excessive use of abbreviations can make the intended information unclear or even confuse the audience. Therefore, the author intends to conduct research on the use of abbreviations in advertisements on social media and its impact on the abilities of eighth-grade students in middle school. Through this research, it is hoped that findings will enrich understanding of the analysis or abbreviation processes and identify the types of abbreviations used. This study applies a qualitative descriptive approach. In this research, the data used consist of all Indonesian vocabulary, sentences, or phrases in advertisements available on social media. The research utilizes data collection techniques such as free observation and note-taking. Based on the data analysis and discussion, two conclusions can be drawn: First, this research identifies four types of abbreviations in social media advertisements: 69 acronyms, 31 initialisms, 11 truncations, and 18 letter symbols. Second, the research identifies 18 abbreviation processes within them.